2011
DOI: 10.1002/acr.20517
|View full text |Cite
|
Sign up to set email alerts
|

Radiographic prognosis of finger joint damage predicted by early alteration in synovial vascularity in patients with rheumatoid arthritis: Potential utility of power doppler sonography in clinical practice

Abstract: Objective. To investigate the relationship between synovial vascularity and progression of structural bone damage in each finger joint in patients with rheumatoid arthritis (RA) and to demonstrate synovial vascularity as a potential therapeutic marker. Methods. We studied 250 metacarpophalangeal (MCP) and 250 proximal interphalangeal (PIP) joints of 25 patients with active RA who were administered adalimumab or tocilizumab. Patients were examined with clinical and laboratory assessments. Power Doppler sonograp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 51 publications
(24 citation statements)
references
References 26 publications
(23 reference statements)
1
21
0
2
Order By: Relevance
“…Synovitis plays an important role in the joint-destroying process. It has been shown that no bone destruction occurs in the absence of synovitis 9 10. Grey-scale US (GSUS) allows a differentiation between exudative and proliferative synovial changes as it provides a good soft-tissue contrast.…”
Section: Introductionmentioning
confidence: 99%
“…Synovitis plays an important role in the joint-destroying process. It has been shown that no bone destruction occurs in the absence of synovitis 9 10. Grey-scale US (GSUS) allows a differentiation between exudative and proliferative synovial changes as it provides a good soft-tissue contrast.…”
Section: Introductionmentioning
confidence: 99%
“…This exploratory study was sized by expert opinion and based on the sample sizes used in numerous radiographic RA studies 6, 12, 13, 14. The baseline temperature discrimination threshold (0.1°F) defines 2 sets of patients, the hot‐joint (≥0.1°F) and cool‐joint (<0.1°F) predictor sets.…”
Section: Methodsmentioning
confidence: 99%
“…However, despite having lower sensitivity and specificity for predicting serious disease, there is a trend toward utilizing laboratory tests and scales to interpret inflammation (e.g., Westergren erythrocyte sedimentation rate [ESR] and C‐reactive protein [CRP] level) or pain (visual analog scale), as well as numerous functional assessment tools (i.e., the Health Assessment Questionnaire [HAQ] and Routine Assessment of Patient Index Data [RAPID3]) 4. Newer approaches like the multibiomarker disease activity test and ultrasound or MRI measurement of joints are quite costly 5, 6, 7. Thus, there is a need for a simple, cost‐effective tool for determining which patients will develop progressive, destructive RA.…”
Section: Introductionmentioning
confidence: 99%
“…Findings from a number of studies investigating the use of ultrasound in daily rheumatologic practice have suggested that ultrasound can be used to monitor therapy in real-life clinical practice settings [2,3,[7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%